Utility of an oral competence questionnaire for patients with facial nerve paralysis. (February 2023) - Charters, Emma; Low, Tsu-Hui (Hubert); Coulson, Susan
Summary: Objective: To investigate the utility of a patient-reported outcome measure that evaluates oral competence; speech and swallowing functions after facial nerve paralysis (FNP). Methods: The Oral Competence Questionnaire (OCQ) covers 16 questions from known, validated patient-reported outcome measures. The OCQ was completed by 40 patients with facial nerve paralysis (FNP) and 40 healthy controls. The sensitivity of the questionnaire was tested against other validated questionnaires for oral function, speech/swallowing functions, and facial nerve-related disability. Normative data were obtained by administering the OCQ to a group of healthy volunteers. Results: A total of 80 participants completed the OCQ (40 FNP and 40 healthy controls). Strong linear relationships (Spearman correlation coefficients >0.8) were observed between speech intelligibility ratings, objective speech outcomes, and the OCQ. Linear correlations were also noted between OCQ and FDI (Spearman correlation coefficient >0.4). The mean OCQ score for participants with FNP was 28.8 and 0.0 for healthy controls. Conclusions: This succinct, 16-item questionnaire demonstrated good sensitivity for testing oral competence and oral function for patients with FNP, and the ability to discriminate between patients with FNP from patients with normal facial nerve function.